Occupational therapy in themanagement of haemophilia patients: A scoping review - Seoane-Martín, Marta Elisa; Cuesta-Barriuso, Rubén; Rodríguez-Martínez, María del Carmen (Wiley, 2024)
Background: Haemophilia is a haematological disease, although most haemorrhages occur in the locomotor system. Patients are physically disabled from an early age and have a poorer perception of quality of life. In the day-to-day lives of patients and their families, psychosocial well-being, the disease’s physical, personal, and social impact, as well as work-related problems are the most complicated aspects of the disease that need to be addressed. Objective: To identify the role of occupational therapy in managing patients with haemophilia and to analyse the therapeutic potential of occupational therapy in treating these patients. Methods: A scoping review was conducted to identify the role of occupational therapy in managing patients with haemophilia and to analyse the therapeutic potential of occupational therapy in treating these patients. The review was registered in the international registry PROSPERO (Id: CRD42022319637). The databases consulted were SCOPUS, PubMed, PsycINFO,Web of Science and Science Direct, including all studies published until 14 August 2023. Results: No single study was found that specifically developed an occupational therapy intervention for patients with haemophilia. Measurement instruments have been identified, specific for patients with haemophilia and generic, that can be useful for the functional evaluation of these patients in the occupational therapy approach.Different studies showed the importance of multidisciplinary treatment, including occupational therapy. Conclusions: The use of occupational therapy could be effective in improving autonomy and quality of life in haemophilia patients. Therefore, it is of paramount importance to conduct research studies within the field of occupational therapy.
Keywords: Hemofilia; Autonomy; Haemophilia; Multidisciplinary treatment; Occupational therapy